Pilot Projects to Secure Local Supply in Rural Areas. Start-ups, Community-oriented Entrepreneurs and Public Funding as Drivers? - Küpper, Patrick; Mettenberger, Tobias; Bermes, Linda (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
The usual store formats can hardly be operated economically in places with fewer than 2,500 inhabitants. In line with the spiral theory, the resulting retreat from the area offers new commercial opportunities for innovative forms of offering, such as staff-free 24/7 markets or online ordering options. At present, a wide variety of actors are experimenting with new and flexible approaches, and it does not yet seem foreseeable which models will ultimately prevail. How can the initial experiences be systematized and what is the potential for establishment? To this end, we compare five pilot projects that use decentralized, mobile and digital formats to bring everyday goods to consumers. For the five case studies, 35 semi-structured interviews were conducted with experts and customers. Central comparative dimensions are the context of emergence and the actor constellations, the contribution to local supply, the economic viability as well as the social function of the offers. The results show that two cases are strongly subsidy-driven or depend on public support. In two other cases, the social function dominates with the involvement of socially oriented enterprises, where the approaches can rather fulfill a complementary supply function. Finally, there is also a new format that at least has the potential to be rolled out on a large scale in rural areas of Germany and beyond.